From partnerships to privatization: the advance of the private sector in brazilian educational policy (Olhar de Professor, 2024)
This paper aims to analyze how trends towards privatization of education in Brazil have showed up in recent years, under the perspective of a documentary and critical analysis, and presents an approach to the notion of endogenous and exogenous privatization, discussed by Ball and Youndell (2007), along with other national and international references. The study discusses how public-private partnerships in education have been created based on contracts, concessions and different forms of privatization that materialize themselves as a set of intentional and oriented strategies based on market logic. The research identified that there is a movement towards the expansion of privatization processes on several fronts of education, in an attempt to appropriate public policies and public funds, configuring itself as an arena for disputes over educational projects and world views that converge to substantiate new meanings to the role of the State.
Keywords: Privatization of education; Educational market; Public and private in education